REVIEW OF STRUCTURE AND APPLICATION IN THREE-AXIS CNC MACHINING: ERRORS, TOOL PATH STRATEGIES, AND EFFICIENCY IMPROVEMENTS - Tayier, Walisijiang (Journal of Engineering & Technological Advances, 2024)
The increasing demands for rapid production have significantly boosted the use of CNC systems in industries. Over the past decade, efforts have concentrated on improving the time efficiency and accuracy of CNC machines. This paper reviews research on CNC machine structures, highlighting common errors such as geometric inaccuracies. It examines advanced tool path generation strategies, including traditional methods and next-generation algorithms like genetic algorithms and the simplex search method. The review assesses these strategies’ impacts on machining efficiency and accuracy, comparing current and historical approaches. The objective is to present a comprehensive overview of advancements in CNC machining, contributing to the development of more efficient, precise, and reliable manufacturing technologies.